SEAWATER INTRUSION AND NITRATE POLLUTION IN COASTAL AQUIFER OF MARATHON BASIN - Papazotos, P.; Koumantakis, I.; Vasileiou, E. (Bulletin of the Geological Society of Greece, 2016)
The overexploitation of groundwater and groundwater salinization cause quantitative and qualitative degradation of the water resources. The objectives of this research are to identify and investigate the extent of seawater intrusion and nitrate pollution into the coastal plain of Marathon in Eastern Attica, Greece. In the frame of this, 25 groundwater samples were collected in October 2014 from the study area and analyzed regarding the main parameters that indicated salinization of the aquifers. Specifically, water chemical analyses were carried out and statistical analyses regarding spatial distribution were performed. The results demonstrated increased values of the parameters which can be associated with seawater intrusion. Considering and evaluating the results from the chemical analyses it is obvious that seawater intrusion takes place in the area. Furthermore, the average concentration of NO3- was 44.16mg L-1 and this can be attributed to overexploitation of coastal aquifer for agricultural activities.